2019
DOI: 10.1136/bmjsem-2018-000431
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography study as a complementary method of screening and prevention of muscle injuries: pilot study

Abstract: ObjectiveTo evaluate thermography application as a complementary method in preventing muscle injury in professional soccer players. MethodsA longitudinal prospective study with 28 professional soccer players that composed a first division of Brazilian’s soccer team between 2015 and 2016. In both seasons (2015 and 2016), muscle injuries were documented and classified in grade of severity, by ultrasound. During the following season (2016), infrared medical thermography was applied twice a week (48 hours after g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 13 publications
3
32
0
5
Order By: Relevance
“…This information is of extreme importance in the planning of the training session that will follow the test application, since it offers the possibility to identify which regions had a higher demand and to plan the session avoiding excessive overload of those regions. In soccer, specifically, studies have sought to verify thermal asymmetries in order to identify and prevent injuries 25 . Regarding the results of thermal asymmetry, it was possible to note that there was no asymmetry in any of the regions analyzed, i.e., there was no contralateral difference greater than 0.3ºC, both before and after the test, indicating that there was no additional overload in none of the body hemispheres, since the differences found (0.1ºC to 0.3ºC) agree with the literature, which classifies asymmetry values <0.5ºC as normal 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This information is of extreme importance in the planning of the training session that will follow the test application, since it offers the possibility to identify which regions had a higher demand and to plan the session avoiding excessive overload of those regions. In soccer, specifically, studies have sought to verify thermal asymmetries in order to identify and prevent injuries 25 . Regarding the results of thermal asymmetry, it was possible to note that there was no asymmetry in any of the regions analyzed, i.e., there was no contralateral difference greater than 0.3ºC, both before and after the test, indicating that there was no additional overload in none of the body hemispheres, since the differences found (0.1ºC to 0.3ºC) agree with the literature, which classifies asymmetry values <0.5ºC as normal 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with other studies that observed the differences in the application of forces between lower limbs did not result in t skin asymmetries [ 40 , 41 ]. Hence, bilateral t skin asymmetries could be more related to the effect of an injury (e.g., inflammatory process or alteration of blood perfusion) [ 17 , 22 ] than with muscular strength imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study pioneered the investigation of possible relationships among the parameters commonly used for the identification of injury risk factors for the thigh muscles (dynamometric parameters) of soccer players and t skin by IRT of hamstrings and quadriceps. Considering previous reports about the importance of a daily IRT asymmetry assessment in injury prevention [ 17 , 19 , 21 , 22 , 23 ], long-term follow-up studies of athletes using IRT evaluation are encouraged. Finally, based on a recent study [ 44 ], further investigations assessing the skin temperature recovery after a cold stress test could add valuable information to the vascularization status of the region analyzed by infrared thermography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological pressure during sports competition disturbs the ideal physical movement and causes injury. Previous reports showed that the incidence of muscle strain in sports is higher during competition than during practice (Dalton et al 2015;Johnson and Comstock 2017;Eckard et al 2017aEckard et al , 2017bCôrte et al 2019). These reports may be attributable to the need for higher-intensity physical movements and stronger muscle contraction to achieve larger or faster movements for better results during competition (Dalton et al 2015;Eckard et al 2017a).…”
Section: Introductionmentioning
confidence: 99%